PERTANGGUNGJAWABAN PIDANA PELAKU TINDAK PIDANA PEMBAKARAN RUMAH DAN ORANG YANG DIDUGA MEMELIHARA ILMU SIHIR PADA KEPOLISIAN RESOR TAPANULI UTARA - IMELDA RIA; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Criminal responsibility of leading to criminal convictions, if you've committed a crime and meet the elements specified in the Act. Looking from the angle of an action that is prohibited (required), someone will be held accountable for such actions when such action is against the law (and no suppression of unlawful or rechtsvaardigingsgrond nature or justification) for it. Seen from the point ability is responsible then only someone who is able to be responsible in the criminal overall responsibility. In fact investigators in North Tapanuli Police, criminal liability has not been implemented properly and do not get a fair sense for some of the injured party. The purpose of this essay writer is to know; First, how the criminal responsibility of the criminal arson, and the person who allegedly maintained witchcraft, second, any obstacle to the criminal responsibility of the criminal arson, and the person who allegedly maintained witchcraft, Third, the efforts of Police North Tapanuli in overcoming obstacles in the implementation of criminal liability criminal arson, and the person who allegedly maintained witchcraft.This research uses juridical sociological look at the correlation between law and society. This research was conducted at the Police North Tapanuli, whereas the sample population is overall the parties relating to the issues examined in this study, the data source used, primary data, secondary data, the data tertiary, data collection techniques in this study with interviews and assessment literature.From the research, there are three main things that can be concluded first, that the criminal responsibility of the criminal arson, and people have not been effective. Due to not all perpetrators of criminal acts in this case subject to strict sanctions, they let loose with a variety of specific reasons. Second, obstacles in the criminal liability considerations are a lot of things done by law enforcement in determining the perpetrators of such crime. Third, the efforts of Police North Tapanuli in overcoming obstacles in the criminal responsibility of the criminal burning of houses and people are doing outreach to rural communities that do not believe in the issue of someone who maintains witchcraft and not vigilante against the alleged.Keywords: Criminal Liability - Burning Houses and People